Vertical Distribution of Phyllosphere Microbial Diversity in a Subtropical Forest: Increase From Canopy to Forest Floor - Yirui Zhang; Lingxiao Wu; Wenjie Li; Jie Wang; Qing Guo; Ya Gao; Renzhi Qin; Shuang Xing; Chang Liao; Chengjin Chu; Xian Yang (Environmental Microbiology, 2026)
The vertical structure of forests creates diverse habitats for microorganisms. Phyllosphere microbial communities, comprising leaf‐associated bacteria and fungi, are key components of forest ecosystems, yet their vertical distribution and assembly processes remain poorly understood. Here, we examined the diversity and composition of phyllosphere microbial communities across five vegetation layers (canopy, subcanopy, interlayer, shrub, and herb) in a subtropical forest in South China, and assessed the contributions of microclimates, host plant traits, and soil‐related factors. We found phyllosphere bacterial and fungal richness increased from the canopy to the forest floor, largely driven by microclimatic variation. Community composition shifted gradually along the vertical gradient, with adjacent layers being more similar. Soil microbial composition and properties explained a large proportion of variation in community composition, particularly for fungi, but their contributions were broadly consistent across vertical layers, with only a slight increase in the herb layer. In contrast, host traits became increasingly important for bacterial communities toward lower strata. These findings reveal clear vertical patterns in phyllosphere microbial diversity and composition, and suggest that distinct combinations of environmental filtering and host‐associated processes shape bacterial and fungal communities across forest strata.